Lymphoma of the Urinary Bladder - Anthony Kodzo-Grey Venyo (Advances in Urology)
Background. Lymphoma of the urinary bladder (LUB) is rare. Aims. To review the literature on LUB. Methods. Various internet databases were used. Results. LUB can be either primary or secondary. The tumour has female predominance; most cases occur in middle-age women. Secondary LUB occurs in 10% to 25% of leukemias/lymphomas and in advanced-stage systemic lymphoma. Less than 100 cases have been reported. MALT typically affects adults older than 60 years; 75% are female. Diffuse large B-cell lymphoma is also common and may arise from transformation of MALT. LUB presents with haematuria, dysuria, urinary frequency, nocturia, and abdominal or back pain. Macroscopic examination of LUBs show large discrete tumours centred in the dome or lateral walls of the bladder. Positive staining of LUB varies by the subtype of lymphoma; B-cell lymphomas are CD20 positive. MALT lymphoma is positively stained for CD20, CD19, and FMC7 and negatively stained for CD5, CD10, and CD11c. LUB stains negatively with Pan-keratin, vimentin, CK20, and CK7. MALT lymphoma exhibits t(11; 18)(q21: 21). Radiotherapy is an effective treatment for the MALT type of LUB with no recurrence. Conclusions. LUB is diagnosed by its characteristic morphology and immunohistochemical characteristics. Radiotherapy is a useful treatment.